Studies in Qumran law and thought - Baumgarten, Joseph M. (Studies on the texts of the desert of Judah, 2022)
The study of the laws of the Dead Sea Scrolls in the light of ancient rabbinic law, and vice versa, by a master of both corpora, sheds light on their interpretation, their history, and the spiritual stances they bespeak. The thirty-two studies united in this volume, a selection of Joseph M. Baumgarten's work in the three decades that followed the appearance of his Studies in Qumran Law (Brill, 1977), focus on legal concerns, both general and detailed, shared by the Qumran sectarians and the ancient rabbis-concerns that elicited responses that were sometimes similar, sometimes different, even to the extent of arousing polemics. An introductory essay by Lawrence H. Schiffman contextualizes the studies and points out the broader themes to which they relate